Description in classical Arabic poetry : waṣf, ekphrasis, and interarts theory - Sumi, Akiko Motoyoshi (Brill studies in Middle Eastern literatures ;, 2004)
This work deals with "wasf" or description which is one of the salient characteristics of the "qasidah" (classical Arabic poetry) tradition. It examines descriptive passages in a selected group of Arabic "qasidah" from different ages, with the motifs of horses, and bees and honey-gathering